Alat Pengukur Deviasi pada KWH Meter 3 Fasa berbasis PZEM 0047 dan Flame Sensor - Indra Ferdiansyah; Epyk Sunarno; Putu Agus Mahadi Putra; Brilianti Qori' Avrila (Jurnal Teknologi Terpadu, 2021)
In the maintenance of Measuring and Limiting Devices (APP) by replacing the kWh Meter on the old kWh meter, as well as P2TL efforts to examine customers who have the potential to commit violations or lack of billing in adjusting electricity rates. In this operation an error / deviation check will be performed on the kWh meter to determine the feasibility of the kWh meter. So far, the measurement of deviation on the kWh Meter 3 Phase is done manually so that it is considered less effective. With this deviation gauge kwh meter 3 phase measurement, meter change officers and P2TL field officers will be able to help in measuring the deviation in the 3 phase kWh meter. This tool reads the power of the kWh meter through the display of the led impulse indicator, then compares it with the power measurement using the metering module at the same time so that the deviation can be detected whether more or less from the meter class, because the measurement standards are based on the meter class. The results obtained from testing on a kWh meter with a grade of 0.5, obtained a deviation of less than 0.5 percent, which means the kWh meter is good because it is still awake in its class according to SPLN No.96 of 1993.Keywords: Deviation, Kwh Meter, Maintaining APP, P2TL